Reconstruction of Marketing Mix Strategy of Educational Services in Creating Superior Customer Value - Suyoko Suyoko; Sulistyorini Sulistyorini; Agus Eko Sujianto (Cahaya Abadi Publisher, 2026)
The dynamics of globalization and market saturation force Private Islamic Religious Colleges (PTKIS) to redefine their marketing strategies to avoid being trapped in partial and secular conventional management. This study aims to analyze and construct a reconstruction of the marketing mix strategy (7P) based on Islamic values ​​in creating superior customer value at the newly established STAI MAS Tulungagung. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed interactively. The results show that STAI MAS successfully deconstructed the 7P elements by integrating the tradition of yellow book literacy (turats), the value of justice ('adl), environmental assurance (hifdzul bi'ah), honest promotion (shiddiq), the work culture of itqan-khidmah, the digital administration system (taisir-amanah), and Islamic aesthetics (nazhafah). This reconstruction has proven to create competitive advantages in the form of public trust and student pride. However, the institution still faces obstacles such as limited digital campaign budgets and public stereotypes about private campuses. Based on these findings, it is recommended that STAI MAS management undertake a more innovative digital transformation and structure integrated marketing communications (IMC) to minimize budget constraints, while optimizing strategic partnerships with Islamic boarding school alumni networks to strengthen the institution's brand equity in suburban areas.